Elephants of Orissa: Conservation Issues and Management Options - Swain, Debabrata; Patnaik, Saroj Kumar (Indian Forester, 2002)
Fifteen elephant habitats have been identified in Orissa and all these habitats lie between 18 ° 50' and 22 ° 19' N latitude and 83 ° 05' and 86 ° 45' E longitude. By water-hole count (1999), Orissa's elephant population was estimated to be 1,827 covering a forest area of 11,167 km2. There were 2,044 elephants in Orissa in 1979. The causes of decline in elephant population are shifting cultivation, encroachment, poaching, mining, forest fire, scarcity of water during dry season, increase in human population, man-elephant conflict, mortality due to diseases, electrocution, legal and administrative inadequacies, etc. In this paper a network of elephant corridors has been suggested for conservation of their population on a long term basis.